Análise sistêmica da comercialização de hortifrutigranjeiros em feiras de agricultura familiar dos territórios sertão do Apodi e Açu-Mossoró (RN) - Azevedo, Melina Bandeira Antas de (2015)
The local fairs of family farming are structures that facilitate the marketing of products in the production chain of fresh produce, expressing the diversification of the segment of family farming. This type of production brings in its history the use of sustainable techniques that enable food and nutritional security like, for example, agroecology, which minimizes environmental impacts on the environment by removing the chemical inputs of production, thus ensuring better quality to food purchased by consumers in addition to the security of livelihoods of family farmers themselves. However, this practice, that was considered a cultural factor of great expression in the country, has been outdated by the surging of large retail chains. So now only a small fraction of the participation in fairs is of family farmers, the assumption being that the dynamics of sustainable family farming of horticultural Açu-Mossoró territories and Sertão do Apodi (RN) still have many weaknesses and the performance of its organization system and its technical production standard are insufficient to trigger the dynamization of the two territories. The aim of this study is, therefore, to demonstrate the importance of the fresh produce chain as new environment for production and innovation in the process of market dynamization. The research is based on the year 2011, prior to the drought faced by the Northeast. The chosen methodology for data collection was of primary data, in order to conduct a census in all family agriculture fairs organized by Projeto Dom Helder Camara, Rede Xique Xique and Associação de Produtores e Produtoras Familiares Agroecológicos de Mossoró (APROFAM) – the association for agroecological family producers from the city of Mossoró. Also, an unstructured interview with the former educational, territorial and political adviser of Diaconia was conducted to understand how was initially conceived the project for the fairs. The research is characterized as comparative, making an integrated analysis between the two territories, with qualitative and quantitative method, since it allows a detailed analysis of the chain marketing process. Secondary data obtained through literature research was also used to corroborate the results. The research was conducted by submitting application forms to all the vendors of these fairs of family farming in the territories of Sertão do Apodi and Açu-Mossoró. It was found that family farmers and fairs play an important role in generating innovation, since they create new ways to improve the quality of life, capitalizing on the remains of production and generating extra income through marketing in the fair, as well as through developed practices that go beyond the conventional model, adopting characteristics that value for sustainability. We have seen that, even with the present insufficient structure, a satisfactory return is obtained, since most producers want to continue or expand the activity. However, this practice is a strategy aimed at resuming a cultural practice that is outdated, providing at least once a week with an environment for material and emotional exchanges, while strengthening a relationship that arouses confidence and values the direct contact between producers and consumers